Pistolas y probetas. El efecto del gasto militar público en i+d. Evidencia con datos de países de la OCDE entre 1985 y 2020 (Journal of the Spanish Institute for Strategic Studies, 2024)
This research tries to bring light to the discussion whether governments should spend or not public resources in military spending, focusing its lens on the relation of this spending and the advancement of R&D. For this, I find out some causal mechanisms that could work as spillovers from the military world to R&D.  I carry out a regression analysis taking data from OECD countries from 1985 to 2020 where I find that there indeed exists a positive relation between military spending and R&D, and that my causal mechanisms are also significant.
Keywords: R&D; military spending; public R&D; patents